2018
DOI: 10.2106/jbjs.cc.18.00168
|View full text |Cite
|
Sign up to set email alerts
|

Type-V Median Nerve Entrapment in a Pediatric Medial Condyle Fracture

Abstract: Case: A 30-month-old boy with a displaced medial condyle fracture and no history of an elbow dislocation was found to have an entrapped median nerve. Conclusion: Entrapment of the median nerve is a potential consequence of a displaced medial condyle fracture, even when there are no neurologic deficits on presentation. This provides additional support for open reduction of these fractures rather than percutaneous treatment or nonoperative management. Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Al-Qattan et al[ 8 ] described a Type 4 impingement in a 14-year-old boy with posterior elbow dislocation and medial epicondyle fracture. In a study by McCarthy et al,[ 6 ] median nerve entrapment has been reported in one case of displaced medial condyle fracture in a young child before medial epicondyle ossification. Although the ulnar nerve is usually injured in medial epicondyle fractures, the median nerve may also be compressed between the apophysis part and the distal humerus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Al-Qattan et al[ 8 ] described a Type 4 impingement in a 14-year-old boy with posterior elbow dislocation and medial epicondyle fracture. In a study by McCarthy et al,[ 6 ] median nerve entrapment has been reported in one case of displaced medial condyle fracture in a young child before medial epicondyle ossification. Although the ulnar nerve is usually injured in medial epicondyle fractures, the median nerve may also be compressed between the apophysis part and the distal humerus.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 ] Median nerve entrapment has been reported in one case of displaced medial condyle fracture in a young child before medial epicondyle ossification. [ 6 ] To the best of our knowledge, the case described, herein, is the first report of median nerve entrapment in medial epicondyle fracture in an adolescent without elbow dislocation. The aim of our study is to reveal that median nerve entrapment due to medial epicondyle fracture may develop in adolescents without elbow dislocation, although it is extremely rare.…”
Section: Introductionmentioning
confidence: 96%
“…Compact bone is supplied by the periosteal and endosteal blood vessels . The periosteal vessels insert into the periosteum, a connective tissue that surrounds the bone.…”
Section: Methodsmentioning
confidence: 99%
“…Incarcerations of the median nerve have also been described in other elbow injuries. McCarthy et al 11 reported on entrapment of the median nerve in a medial condyle fracture, and several authors have published cases of intra-articular median nerve entrapment after elbow dislocation.…”
Section: Introductionmentioning
confidence: 99%